COVID-19 Positive Woman Presented with Preterm Labor: Case Report - Ibrahim A. Abdelazim; Mohannad AbuFaza; Sulaiman Al-Munaifi (Gynecology Obstetrics & Reproductive Medicine)
The novel coronavirus disease-19 (COVID-19) considered a global health problem. Pregnant women are considered a COVID-19 high-risk group. A 26-years old woman, G2 P1+0, previous cesarean section, 31 weeks`+4 days, admitted with preterm labor, without fever, cough, and/or respiratory symptoms on admission. She presented to the emergency department with fever, and cough, 27 days before the current admission, she was referred to the Ministry of Health, and her COVID-19 PCR swab at Ministry of Health was positive. She delivered by cesarean section, and the PCR swab of the studied woman taken on admission came positive for COVID-19. The delivered girl was admitted to the neonatal intensive care unit for 16 days. The PCR swab of the delivered girl came negative for COVID-19. This report highlights that the COVID-19 infection during pregnancy may increase the rates of preterm labor and cesarean section. There is no strong evidence of vertical COVID-19 transmission when the infection manifests during the 3rd trimester of pregnancy.